Quenya is Practically a Main Character - Gloria Comandini; Francesco Dedè (RiCognizioni, 2025)
In the last forty years, fan fictions, derivative writings openly based on published works of fiction, have gone from being shared on semi-secretive zines circulating between a handful of people, to being hosted on public online archives, such as Archive of Our Own with 6 million registered users. At the same time, fan studies have grown into an interdisciplinary and transnational field. However, linguistic approaches to fan studies and fan fictions have always been quite marginal, and even more rare are the linguistic works investigating the use of conlangs in fan fictions.